Management and Manager in Information Centers as an Organization - Malik Yılmaz (Türk Kütüphaneciliği)
In this paper the working of management process in Information centers, as a formal service giving organization is studied. Management process is evaluated generally and management-information centers relationship, the role of the manager, with influencing elements are discussed.